The Difference of Compliance Cost Before and After Using E-Filing Application on Company Taxpayers E-Filing User - Vania Wimayo (Akuntabilitas, 2019)
The purpose of this study was to determine differences in compliance cost incurred before and after the use of E-Filing applications for corporate tax payers E-Filing users.E-Filing Tax Return is a reporting system created by the DGT which makes it easy for taxpayers in the manufacture and delivery of Tax Return report to the Director General of Taxation. The hypothesis in this study was tested using the Wilcoxon test match pairs. The type of data used in this study is quantitative data. The research method used is a survey and the instrument used to collect data is a questionnaire. The results show that compliance cost after the use of e-filing in contrast to earlier, where the compliance cost will be lower.